THE USE OF NITRIC ACID AS A PERLITE ACTIVATOR IN ADSORBING METHYLENE BLUE - Mardiana Rimba Utami; Kapti Riyani; Tien Setyaningtyas (Tanjungpura University, 2023)
Industrial activities in modern times that are growing rapidly can cause environmental problems. This is due to the increasing amount of waste generated due to increased production. Untreated dye waste can inhibit sunlight penetration, photosynthesis activity, and the growth of aquatic biota. One of the dye wastes that is often found is methylene blue. Processing of methylene blue dye can use a practical adsorption method, easy to do at a low cost. This study showed the results of methylene blue adsorption using activated perlite nitric acid adsorbent. The best activity of perlite in adsorbing methylene blue is at pH 9 with a contact time of 180 minutes which results in a maximum adsorption capacity of 3,873 mg/g. The adsorption kinetics used followed a pseudo second order-model with consecutive k and q values of 0.0055 g/mg.min and 3.3102 mg/g, while the adsorption isotherms followed the Langmuir isotherm model with qmax and KL values of 3.873 mg/g and 0.5822 L/mg, respectively.